Uncovering the Response of Property Stock Returns to Inflation, Interest Rates, and Exchange Rate Shocks 2021–2024 - Muwahhidin, Didin; Apritoba, Henokh Ziw (Klabat Accounting Review, 2026)
understanding that accounting functions as an economic language that reflects the influence of macroeconomic factors on company performance and value in the capital market. Fluctuations in stock returns in the property sector in Indonesia during the 2021–2024 period, amidst dynamics of inflation, interest rates, and exchange rates that are not always in line with theory or previous empirical findings, raise questions about the influence of these three variables on stock returns. This study aims to analyze the influence of inflation, interest rates, and exchange rates on stock returns of property companies listed on the Indonesia Stock Exchange using the Arbitrage Pricing Theory (APT) framework. A quantitative approach with a causal associative design was used in this study, with secondary data sourced from the Indonesia Stock Exchange and Bank Indonesia. The research sample consisted of two property sector issuers with monthly data for the 2021–2024 period. Data analysis was performed using the SEM-PLS method through the WarpPLS application. The results show that inflation and interest rates have no significant effect on stock returns, while the exchange rate has a negative and significant effect. These findings indicate that the property sector is more sensitive to exchange rate changes than other macroeconomic variables.